PENGARUH PENGUNGKAPAN ESG TERHADAP TINGKAT PERTUMBUHAN BERKELANJUTAN PERUSAHAAN DENGAN MANAJEMEN MODAL KERJA SEBAGAI VARIABEL MODERATING (Studi Empiris Pada Perusahaan Sektor Consumer Non-Cyclicals Yang Terdaftar Di Bursa Efek Indonesia Periode Tahun 2020 – 2024) - Rachma Nur Wulandari; Mutiara Tresna Parasetya (Diponegoro Journal of Accounting, 2026)
This study aims to analyze the effect of Environmental, Social, and Governance (ESG) disclosure on Sustainable Growth Rate (SGR) with Working Capital Management (WCM) as a moderating variable and Return on Assets (ROA) and firm size as control variables in Consumer Non-Cyclicals sector companies listed on the Indonesia Stock Exchange during the period 2020–2024. This research uses a quantitative approach with panel data regression analysis using a Two-Way Fixed Effects model. The sample consists of 7 companies with a total of 35 observations selected through purposive sampling based on data availability during the observation period.The results show that ESG has a positive and significant effect on SGR, indicating that higher ESG disclosure increases the firm’s sustainable growth rate. Meanwhile, Working Capital Management (WCM) is found to moderate the relationship between ESG and SGR in a negative direction, thereby weakening the effect of ESG on sustainable growth. Furthermore, Return on Assets (ROA) and firm size as control variables are also found to have a positive and significant effect on SGR. These findings indicate that internal firm factors remain important determinants of sustainable growth. This study implies that ESG implementation should be accompanied by efficient working capital management in order to optimize sustainable growth.